2018
DOI: 10.3390/ma11112201
|View full text |Cite
|
Sign up to set email alerts
|

On the High Formability of AZ31-0.5Ca Magnesium Alloy

Abstract: In this work, we investigated the effect of Ca on the formability of the AZ31 Mg alloy. For this purpose, the microstructure, texture, mechanical properties and formability of AZ31 Mg alloy samples containing 0.5 wt. % Ca (AZ31-0.5Ca) were studied. For comparison, the performance of Ca-Free AZ31 alloy samples with similar grain size was also investigated. In addition, formability of this alloy was reached at a high punch speed. The results of this work showed that the addition of 0.5 wt. % Ca can enhance the f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 28 publications
(11 citation statements)
references
References 46 publications
1
10
0
Order By: Relevance
“…A great deal of work has been dedicated to developing a technological procedure capable of weakening the basal texture and/or reducing the critical resolved shear stresses (CRSS) of the non-basal slip systems. Among those, specific alloying, primarily with Rare Earth elements [80] (with regard to the present work, it should be noticed that the addition of calcium into the Mg-Zn system also weakens the strong basal textures and promotes grain refinement during hot-extrusion of Mg-Zn-Ca and Mg-Zn-Al-Ca alloys due to the particle stimulated nucleation of dynamic recrystallization [81,82]), and imposing shear deformation, e.g., via asymmetrical rolling [83] or ECAP [75,[84][85][86] have gained the greatest popularity. Agnew et al [87,88] have shown that the texture becomes stronger with the increasing number of ECAP-Bc passes.…”
Section: Texture Analysismentioning
confidence: 82%
“…A great deal of work has been dedicated to developing a technological procedure capable of weakening the basal texture and/or reducing the critical resolved shear stresses (CRSS) of the non-basal slip systems. Among those, specific alloying, primarily with Rare Earth elements [80] (with regard to the present work, it should be noticed that the addition of calcium into the Mg-Zn system also weakens the strong basal textures and promotes grain refinement during hot-extrusion of Mg-Zn-Ca and Mg-Zn-Al-Ca alloys due to the particle stimulated nucleation of dynamic recrystallization [81,82]), and imposing shear deformation, e.g., via asymmetrical rolling [83] or ECAP [75,[84][85][86] have gained the greatest popularity. Agnew et al [87,88] have shown that the texture becomes stronger with the increasing number of ECAP-Bc passes.…”
Section: Texture Analysismentioning
confidence: 82%
“…The XRD results of the TRC condition imply the occurrence of Mg 2 Ca precipitates, which can act as nucleation sites for recrystallization. The addition of calcium contributes to the formation of the Mg 2 Ca phase [35,36]. XRD results reveal, that precipitates have dissolved during heat treatment at 460 °C, because only α-magnesium matrix was detected.…”
Section: Discussionmentioning
confidence: 99%
“…The addition of Ca to Mg-Al-alloys leads to various beneficial effects for wrought alloys, for example, reduced anisotropy [101,102], reduced grain size [103], increased creep resistance [104,105] and the ability of precipitation hardening by Mg 2 Ca and Al 2 Ca intermetallic phases [8]. Additionally, the oxidation tendency of Mg is reduced when Ca is present in the alloy [106][107][108], reducing possible fire hazards during alloy preparation, melt handling and high temperature processing (e.g., heat treatment, forging, ...).…”
Section: Mg-al-ca-systemmentioning
confidence: 99%